CREATIVE APPROACH TO PEDAGOGICAL ACTIVITY (Web of Teachers: Inderscience Research, 2024)
Creativity (lat., ing. "create"-creative, "creative" means the creative ability of an individual, which describes the readiness to produce new ideas and is part of talent as an independent factor). This article provides information about the importance of creativity in pedagogical activities.